2009
DOI: 10.1080/10673220902742476
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Long-Term Psychoanalytic Therapy: A Systematic Review of Empirical Studies

Abstract: Background: There is a gap in the research literature on the effectiveness of long-term psychoanalytic therapies (LPT). Aim: To present a systematic review of studies dealing with LPT effectiveness and published from 1970 onward. Methods: A systematic literature search for studies dealing with the effectiveness of individual LPT in ambulatory, adult patients. Data about the overall effectiveness of LPT, its impact on symptom reduction, and its effect on personality changes were pooled both at treatment termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(103 citation statements)
references
References 60 publications
4
88
0
11
Order By: Relevance
“…In the field of psychodynamic treatment of adults this situation began to change in recent years, with the publication of a number of important reviews and meta-analyzes (De Matt, Jonghe, Schoevers & Dekker, 2009;Gerber et al, 2011;Leichsenring, 2005;Leichsenring & Rabung, 2008;Leichsenring, Rabung, & Leibing, 2004;Shedler, 2012;Town, Diener, Abbass, Leichsenring, Driesse, & Rabung, 2012). Based on Randomized Controlled Trials (RCT) or not, these revisions showed that psychodynamic psychotherapy is at least equal to other forms of treatment regarded as evidence-based and that patients receiving this treatment not only keep the gains after its end, but often continue to improve.…”
mentioning
confidence: 99%
“…In the field of psychodynamic treatment of adults this situation began to change in recent years, with the publication of a number of important reviews and meta-analyzes (De Matt, Jonghe, Schoevers & Dekker, 2009;Gerber et al, 2011;Leichsenring, 2005;Leichsenring & Rabung, 2008;Leichsenring, Rabung, & Leibing, 2004;Shedler, 2012;Town, Diener, Abbass, Leichsenring, Driesse, & Rabung, 2012). Based on Randomized Controlled Trials (RCT) or not, these revisions showed that psychodynamic psychotherapy is at least equal to other forms of treatment regarded as evidence-based and that patients receiving this treatment not only keep the gains after its end, but often continue to improve.…”
mentioning
confidence: 99%
“…Therefore, numerous studies have been carried out in recent years on the effectiveness of psychodynamic therapies, and the findings support the effectiveness of this therapy on mild and complex mental health problems (1). Meta-analyses show the impact of psychodynamic therapies on the symptoms of many psychiatric disorders, for example, personality disorders (17), Depression (18,19), Schizophrenia (20,21); and even in long-term psychoanalytic therapy (2,22,23). But Kazdin (24) believes that no evidence-based explanation can be offered on how and why the intervention of a psychodynamic psychotherapist can result in changes in patients, and more research is needed on the mechanisms of change and variables involved in the effectiveness of the psychodynamic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence supporting the effectiveness of LTDP and psychoanalysis (de Maat et al 2009), especially in long-term follow-ups (Knekt et al 2008(Knekt et al , 2011Huber et al 2013). There is also some indirect evidence that LTDP is superior to other psychotherapies in treating complex patients with chronic depression and previous treatment failures (Leichsenring & Rabung, 2008, 2010Fonagy et al in press).…”
Section: Long-term Dynamic Psychotherapy (Ltdp)mentioning
confidence: 99%